Cruzamiento del fríjol [conjunto audiotutorial] - Campos Segura, Ricardo; Flor Montoya, Carlos A.; Ospina O., Héctor Fabio; Temple, S. (International Center for Tropical Agriculture, 1977)
This audiotutorial unit (cassette, printed script, 139 color slides, study guide, self-evaluation test), prepared by the Communications Support Unit at CIAT, is available for use with a manually or automatically synchronized slide projector/cassette tape recorder. Each unit is available from the Distribution Office at a cost of US$$50; photocopies of the study guide alone can be obtained from the Bean Information Center. Hybridization or crossing constitutes the principal means for genetic improvement of plants. Basic concepts of the morphology of the bean flower, floral bud, self-fertilization, emasculation, hybridization or crossing, materials and equipment used are reviewed. The following techniques are described: hybridization by emasculation with the stigma covered and uncovered, and hybridization without emasculation. Factors affecting the efficiency of hybridization are discussed. (CIAT)